Accessibility and Usability of Information and Technology Communication: Application for Record-Keeping among Secondary School Administrators - Hammed Olalekan Bolaji; Bashirat Funmilayo Ibrahim (Universitas Pendidikan Indonesia (UPI), 2023)
This study examined the accessibility and usability of Information and Technology Communication: Application for record-keeping among secondary school administrators in Ilorin Metropolis, Kwara State. The findings of this study revealed the information and communication technology (ICT) facilities available, accessible and usable for record-keeping among secondary school administrators in Ilorin Metropolis, Kwara, Nigeria, including general computers, laptops, CD ROMs, DVD ROMs, flash drives, and scanners. there is no significant difference between the mean score of male and female secondary school administrators in the area of accessibility and usability of Information and Technology Communication facilities for record-keeping in Ilorin Metropolis, Kwara State. Based on the findings, it was recommended that There should be adequate provision of modern ICT facilities for record-keeping among secondary school administrators in Ilorin Metropolis, Kwara State. The government should enhance the proper accessibility and usability of Information and Technology Communication facilities in record keeping and other areas of school activities by procuring funds for the purchase of these new technology devices and training staff and school administrators for effective use of these facilities.